The Normal Static Two-Point Discrimination in the Palmar Aspect of Hand in Adults and Children in a Sample Indian Population - S.K. Pandian K.; M.R. Thatte; Pawan Agarwal; S. Rajendran; Mohamed Ibrahim; Vishnu Babu G; Latha Madhavan; A.N. Sharma; Bipin Ghanghurde; Anand Dugad; Onkar Kulkarni; Harsh R. Shah; et al. (Indian Journal of Plastic Surgery)
Background The normal ability to distinguish two points from one is known as the two-point discriminative (2PD) sense. This forms an extremely important assessment in patient with injuries to the nerves distributed to the upper extremity.